2020
DOI: 10.1080/19490976.2020.1801944
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress tolerance and antioxidant capacity of lactic acid bacteria as probiotic: a systematic review

Abstract: Lactic acid bacteria (LAB) are the most frequently used probiotics in fermented foods and beverages and as food supplements for humans or animals, owing to their multiple beneficial features, which appear to be partially associated with their antioxidant properties. LAB can help improve food quality and flavor and prevent numerous disorders caused by oxidation in the host. In this review, we discuss the oxidative stress tolerance, the antioxidant capacity related herewith, and the underlying mechanisms and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(214 citation statements)
references
References 201 publications
3
165
1
1
Order By: Relevance
“…Probiotic strains (live and heat treated cells) exert antioxidant activity, reducing damage caused by oxidative stress [ 31 , 32 , 33 , 34 ]. Moreover, previous studies have demonstrated that probiotics strains are able to exert antioxidant effect on the nematode C. elegans [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic strains (live and heat treated cells) exert antioxidant activity, reducing damage caused by oxidative stress [ 31 , 32 , 33 , 34 ]. Moreover, previous studies have demonstrated that probiotics strains are able to exert antioxidant effect on the nematode C. elegans [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Probiotic strains have been reported to help maintain the homeostasis of intestinal function, by regulating the expression of TJ proteins at cell boundaries, reducing adverse effects of pathogens, and protecting them from oxidative stress-induced damage, by scavenging ROS and/or preventing their formation while modulating inflammatory cascades [ 9 , 31 , 34 ]. Similarly, beneficial properties have been documented in non-viable probiotics, including anti-inflammatory, anti-pathogen adhesion, and gut barrier function attributes [ 6 , 10 , 14 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is demand for incorporation of temperature-and moisture-stable probiotics and prebiotics into novel foods and supplements, in increasing levels and complex combinations. This trend has placed a burden on the evolution of quality assurance methodologies to ensure stability, shelf life, batch consistency, and functional integrity of such bioactive ingredients [113][114][115]. Over the years, numerous studies have called into question the quality and purity of commercial probiotic products [116], and calls have been made for standardised assessment and certification tools to improve trust from end users and other stakeholders [2].…”
Section: Quality Assurance Developmentsmentioning
confidence: 99%
“…Mishra et al [ 7 ] briefly reviewed some probiotic strains’ antioxidant properties, but they failed to dig into the pathways and signaling mechanisms followed by them to suppress oxidative stress. In comparison, Feng et al [ 8 ] reviewed the antioxidant capacity, mechanisms, and signaling pathways followed by probiotic bacteria to overcome oxidative damage. They also discussed the genes associated with lactic acid bacteria (LAB) redox potential and suitable methods to evaluate LAB’s antioxidant capacity, yet the current research scenario’s information is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we discuss the antioxidant potentials of yeast and protozoa with a detailed description of peroxiredoxins (Prxs) from yeast. Though many studies are available on microorganisms’ antioxidant potential [ 6 , 8 , 15 , 16 ], there have been comparatively very few studies that illustrate the various antioxidant bioactive compounds from microbial sources and their mode of action to scavenge free radicals. We analyse the signaling pathways by which mycothiol, astaxanthin, LAB, and Prxs to cope up with oxidative stress and finally summarize the prospect and challenges to be overcome to find out novel and potent antioxidant microbial compounds.…”
Section: Introductionmentioning
confidence: 99%